An electro-pulse mediated electrochemical carbon capture type nitrogen-rich copper-based catalyst and a preparation method and application thereof

CN121915448BActive Publication Date: 2026-10-23TONGJI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610386141.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-27
Publication Date
2026-10-23
Estimated Expiration
2046-03-27

AI Technical Summary

Technical Problem

[0006]鉴于上述现有技术的不足,本发明旨在提供一种电脉冲介导的电化学碳捕获(ECC)型富氮铜基催化剂及其制备方法与应用,通过催化剂结构设计与反应调控策略协同,解决现有电催化体系中CO2与NO3-还原路径竞争、反应物时空分布不可控、尿素产率低且能耗高的核心技术问题

Benefits of technology

(1)定制Cu/Cu2O@NCS核壳催化剂,构建动态响应集成系统,实现电化学碳捕获(ECC)与时空程序设计的协同创新。壳层sp2-杂化吡啶氮位点具 redox活性,可在还原电位下捕获CO2形成储库,同时Cu/Cu2O核将硝酸盐预还原为*NOx中间体,为耦合反应奠基。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121915448B_ABST
    Figure CN121915448B_ABST
Patent Text Reader

Abstract

The present application relates to an electric pulse mediated electrochemical carbon capture type nitrogen-rich copper-based catalyst and its preparation method and application. The catalyst described in the present application is a Cu / Cu2O@NCS core-shell structure, the core phase is a Cu / Cu2O composite phase, and the shell layer is a nitrogen-rich carbon layer rich in sp 2 Hybrid pyridine nitrogen sites. By Stober method, calcination doping and activation of the preparation, the performance advantage is verified by the preparation of nitrogen-free doping control sample. The catalyst is integrated with the ECC function and the pulse potential regulation to build a dynamic response system, realizes the spatiotemporal precise conversion of CO2 capture-release, and reconstructs the competitive path of CO2 and nitrate reduction into an orderly series reaction to direct promote C-N coupling to generate urea. The present application overcomes the problems of low urea yield, difficult reactant regulation and high energy consumption of existing catalysts, and the urea yield reaches 36249 mu g.h ‑1 ·mg ‑1 Under the optimized pulse potential, reduces nearly 31% energy consumption, and can realize nearly zero carbon emission with industrial nitrate wastewater as nitrogen source, providing a new paradigm for green urea electrocatalytic synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalysis technology, and in particular to an electropulse-mediated electrochemical carbon capture (ECC) type nitrogen-rich copper-based catalyst, its preparation method and application, especially suitable for the reaction system of electrocatalytic synthesis of urea from carbon dioxide and nitrate. Background Technology

[0002] Urea is an indispensable fertilizer and a multifunctional chemical crucial to global agriculture and food security. Currently, industrial urea production mainly relies on a multi-step reaction of N2+H2→NH3 and NH3+CO2→CO(NH2)2. This not only requires harsh synthesis conditions but also results in large amounts of carbon dioxide emissions, significantly increasing the environmental burden and carbon footprint. Therefore, developing a green and sustainable urea synthesis pathway is urgently needed.

[0003] Carbon dioxide (CO2) and nitrate (NO3) - Using [a specific method] as a raw material, the electrocatalytic synthesis of urea provides a mild and sustainable alternative to chemical production. This method can significantly reduce the carbon footprint of traditional industrial thermochemical production and achieve the resource conversion of carbon dioxide, nitrogen resources, and nitrate nitrogen in wastewater, thus possessing both environmental value and resource recycling significance. However, NO3 [is a concern]. - The process of generating urea by electrocatalytic coupling with CO2 involves two core steps: reactant electroactivation and intermediate CN coupling. These two steps overlap spatially but are not synchronized in time. In addition, the low efficiency of CO2 supply and the difficulty in controlling the utilization process often lead to insufficient carbon source supply to the active sites. The reaction is easily dominated by nitrate reduction reaction, which restricts the yield of urea electrosynthesis.

[0004] Currently, traditional concentration-enhancing strategies such as gas diffusion electrodes can improve CO2 accessibility to some extent, but they suffer from a deep-seated drawback: the inability to precisely control the spatiotemporal distribution of reactants. Due to the lack of precise control over the reaction pathway, urea yield has consistently struggled to break through bottlenecks. This indicates that simply improving carbon dioxide accessibility is far from sufficient; the core challenge lies in achieving precise spatiotemporal control of carbon dioxide transport and conversion, specifically targeting CO2 and NO3. - This essentially parallel competitive response is restored and reconstructed into an orderly, sequential process.

[0005] Copper-based catalysts in CO2 and NO3 - All showed good potential in reduction reactions, including Cu. + The site can moderately adsorb CO intermediates and can bind NO3 through electrostatic interactions. - It also weakens the NO bond and is recognized as a key active site for promoting CN coupling. In existing studies, the urea yield of Cu2O-based catalysts is only 632.1-1908 μg·h⁻¹. -1 ·mg-1 While progress has been made in catalytic carbon capture (CAT), high yields remain elusive due to limitations in catalyst structure and reaction control mechanisms. In recent years, emerging electrochemical carbon capture technologies, utilizing redox-tunable adsorbents (such as nitrogen-rich Lewis base sites), have provided a novel approach for constructing dynamically enriched CO2 microenvironments at catalyst interfaces by reversibly capturing and releasing CO2 through potential changes. However, current technologies still lack an integrated catalytic system capable of precisely controlling the spatiotemporal supply of reactants and the orderly regulation of reaction pathways, severely hindering performance improvements in urea electrocatalytic synthesis. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide an electropulse-mediated electrochemical carbon capture (ECC) type nitrogen-rich copper-based catalyst, its preparation method and application, and solves the problem of CO2 and NO3 in existing electrocatalytic systems through the synergistic effect of catalyst structure design and reaction regulation strategies. - The core technical challenges include competition for reduction pathways, uncontrollable spatiotemporal distribution of reactants, low urea yield, and high energy consumption.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first objective of this invention is to provide an electropulse-mediated electrochemical carbon-capturing nitrogen-rich copper-based catalyst, wherein the electrochemical carbon-capturing nitrogen-rich copper-based catalyst comprises a core-shell structure Cu / Cu2O@NCS, with a Cu / Cu2O composite phase as the core and a nitrogen-rich sp2O@NCS. 2 - The nitrogen-rich carbon layer with hybridized pyridine nitrogen sites forms a shell; in the Cu / Cu2O composite phase, Cu + The site is a key active site that promotes CN coupling. This structure can simultaneously achieve programmable CO2 capture-release and targeted activation of reactants.

[0008] In some embodiments of the present invention, the thickness of the shell layer is 20-30 nm; The particle size of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst is 100-500 nm; The loading of copper in the electrochemical carbon-capturing nitrogen-rich copper-based catalyst is 5-15 wt%.

[0009] A second objective of this invention is to provide a method for preparing the aforementioned pulse-mediated electrochemical carbon-capturing nitrogen-rich copper-based catalyst, comprising the following steps: S1. Mix silicon source with ethanol to obtain solution A; add alkaline substance to the mixed solvent to obtain solution B; mix solution A and solution B and react, then add formaldehyde solution and resorcinol, react at room temperature for 20-26 hours to obtain a mixed solution; heat the obtained mixed solution to obtain a carbon shell precursor. S2. The obtained carbon shell precursor is mixed with a nitrogen source and calcined in an inert atmosphere. After cooling, the sample is placed in a template removal agent solution and stirred to obtain a nitrogen-doped carbon shell. S3. Disperse the copper source and the obtained nitrogen-doped carbon shell in a mixed solution, heat to evaporate the solution, and calcine the obtained solid under an inert atmosphere to obtain the pulse-mediated electrochemical carbon capture type nitrogen-rich copper-based catalyst.

[0010] In some embodiments of the present invention, in step S1, the silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, and tetrabutyl orthosilicate; The alkaline substance includes one or more of concentrated ammonia, triethylamine, and ethanolamine; The mixing reaction time is 1.5-2.5 hours; The mixed solvents include deionized water and ethanol; The concentration of the alkaline substance is 25-28 wt%; The concentration of the formaldehyde solution is 37-40 wt%; The volume-to-mass ratio of the formaldehyde solution to resorcinol is (5.0-6.2):(3.5-4.5) mL / g; Heating reaction: temperature 90-110℃, time 22-26h.

[0011] In some embodiments of the present invention, in step S2, the nitrogen source includes melamine and / or dicyandiamide; The mass ratio of the carbon shell precursor to the nitrogen source is 1:4-6; Inert gases in an inert atmosphere include nitrogen and / or argon; Calcination conditions: heating rate of 8-12℃ / min, calcination temperature of 650-750℃, and calcination time of 0.8-1.2h; The template removal agent solution includes one or more of potassium hydroxide solution, sodium hydroxide solution, and hydrofluoric acid solution; The concentration of the potassium hydroxide solution is 4-6M; The stirring time is 8-10 hours.

[0012] In some embodiments of the present invention, in step S3, the copper source is selected from one or more of hydrated copper nitrate, copper chloride, copper sulfate, and copper acetate; The mass ratio of the copper source to the nitrogen-doped carbon shell is (5~30):1; The mixture comprises water and methanol in a volume ratio of (4-6):(6-9). The heating temperature is 75-85℃; The inert gas in the inert atmosphere is selected from nitrogen and / or argon; Heating and roasting conditions: heating rate of 4-6℃ / min, temperature of 380-420℃, and time of 1.8-2.2h.

[0013] A third objective of this invention is to provide an application of an electropulse-mediated electrochemical carbon-capturing nitrogen-rich copper-based catalyst in the electrocatalytic synthesis of urea from carbon dioxide and nitrate. This invention achieves precise spatiotemporal supply of reactants and control of the reaction pathway through the synergistic effect of electrochemical carbon capture and pulse potential modulation.

[0014] In some embodiments of the present invention, the application includes the following steps: The electrochemical carbon-capturing nitrogen-rich copper-based catalyst, binder, and conductive agent are mixed, and a solvent is added to form a slurry. This slurry is then coated onto the surface of a conductive substrate and vacuum dried to obtain the working electrode. A three-electrode system was constructed using the working electrode as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. An H-type electrolytic cell or a flow cell was used as the reaction device, a mixed solution of bicarbonate and nitrate was used as the electrolyte, and carbon dioxide was introduced. Applying a pulsed potential mode of current, with a negative potential range of -0.6V to -0.4V (relative to the reversible hydrogen electrode, vs RHE), achieves CO2 capture and nitrate pre-activation. The oxidation potential range of 0.3V to 0.47V (relative to the reversible hydrogen electrode, vs RHE) releases CO2 and triggers the CN coupling reaction.

[0015] In some embodiments of the present invention, the mass ratio of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst, binder, and conductive agent is (8-9):(0.5-1):(0.5-1). The coating amount of the slurry is 0.05-2 mg / cm². 2 The vacuum drying temperature is 60-80℃, and the time is 8-12 hours; The binder is one or more of Nafion reagent, polyvinylidene fluoride, or perfluorosulfonic acid resin; the conductive agent is acetylene black and / or Ketjen black; the conductive substrate is carbon paper or copper foil. The electrolyte contains 0.1-1.5 M of bicarbonate and 0.05-1.0 M of nitrate. The bicarbonate is potassium bicarbonate and / or sodium bicarbonate, and the nitrate is one or more of potassium nitrate, sodium nitrate, and industrial nitrate wastewater.

[0016] The sources of the nitrate include one or more of industrial nitrate wastewater, potassium nitrate, and sodium nitrate; the industrial nitrate wastewater is nitrate-rich wastewater from chemical wastewater, electroplating wastewater, or agricultural runoff, which can be directly used as a nitrogen source to replace pure nitrate, thereby achieving wastewater resource utilization and near-zero carbon emissions.

[0017] To further enhance environmental value and resource utilization, industrial nitrate wastewater can be used directly to replace pure nitrate as a nitrogen source.

[0018] In some embodiments of the present invention, in the pulse potential mode, the duration of each potential interval is 10-60s, and the pulse period is 20-120s; during the reaction, the electrolyte temperature is controlled at 25-60℃, and the carbon dioxide introduction rate is 10-50mL / min.

[0019] In some specific embodiments of the present invention, the specific preparation method of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst includes the following steps: (1) Preparation of carbon shell precursor (CS): Using the typical Stöber method, 30-40 mL of tetraethyl orthosilicate (TEOS) was mixed with 280-320 mL of ethanol and stirred until homogeneous to obtain solution A; at the same time, 30-38 mL of concentrated ammonia was added to a mixture of 50-70 mL of deionized water and 140-160 mL of ethanol and stirred until homogeneous to obtain solution B. Under vigorous stirring at 350-450 rpm, solution A was added dropwise to solution B, and the reaction was continued for 1.5-2.5 h after the addition was completed; then 5.0-6.2 mL of formaldehyde solution and 3.5-4.5 g of resorcinol were added to the mixture in sequence, and the reaction was continued at room temperature for 20-26 h. After the reaction was completed, the mixture was transferred to a 180-220 mL PTFE-lined stainless steel reactor and reacted at 90-110 °C for 22-26 h. After cooling to room temperature, the obtained sample was washed three times by alternating centrifugation with deionized water and anhydrous ethanol, and then vacuum dried at 55-65 °C to obtain the carbon-shell precursor (CS). The concentration of concentrated ammonia was 25-28 wt%, the formaldehyde solution was 37-40 wt%, and the ethanol was of analytical grade.

[0020] (2) Preparation of nitrogen-doped carbon shell (NCS): The carbon shell precursor (CS) obtained in step A was mixed with melamine at a mass ratio of 1:4-6, placed in a covered crucible, and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was increased to 650-750℃ at a heating rate of 8-12℃ / min, and calcined at a constant temperature for 0.8-1.2h. After calcination, the tube furnace was allowed to cool naturally to room temperature, and the sample was removed. The sample was placed in a 4-6M potassium hydroxide solution and stirred for 8-10h to remove some of the silica template. After the reaction was completed, the sample was centrifuged, washed until the filtrate was neutral, and vacuum dried to obtain nitrogen-doped carbon shell (NCS). To construct a control sample, a series of nitrogen-doped carbon shell samples were also prepared at calcination temperatures of 550℃, 800℃, and 1000℃. The preparation process was the same as above except for the calcination temperature.

[0021] (3) Preparation of nitrogen-doped carbon shell-coated Cu / Cu2O catalyst (Cu / Cu2O@NCS): Weigh an appropriate amount of copper nitrate trihydrate and 0.18-0.22g of NCS obtained in step B, disperse them in a mixed solution of 8-12mL deionized water and 12-18mL methanol, and control the copper loading in the catalyst to be 5-15wt%. Heat the mixed solution in an environment of 75-85℃ until the water is completely evaporated to obtain a solid mixture. Place the solid mixture in a tube furnace and heat it to 380-420℃ at a heating rate of 4-6℃ / min under a nitrogen atmosphere, calcine at a constant temperature for 1.8-2.2h, and obtain the Cu / Cu2O@NCS catalyst after natural cooling. To construct a control sample, a series of catalysts with copper loadings of 5wt%, 20wt%, and 30wt% were also prepared. The preparation process was the same as above except for the amount of copper nitrate trihydrate.

[0022] The technical solution of the present invention has the following advantages over the prior art: (1) Customized Cu / Cu2O@NCS core-shell catalysts were developed to construct a dynamic response integrated system, achieving synergistic innovation between electrochemical carbon capture (ECC) and spatiotemporal programming. (shell sp) 2 - The hybrid pyridine nitrogen site exhibits redox activity, enabling it to capture CO2 at reduction potential to form a reservoir, while the Cu / Cu2O core pre-reduces nitrate to *NO. x Intermediates lay the foundation for coupling reactions.

[0023] (2) Precise real-time air conditioning of CO2 is achieved by dynamically programming the core-shell interface microenvironment through pulse potential. High-concentration CO2 pulses are released at oxidation potential to ensure the proper mixing of *COOH and *NO. x The intermediates are in full contact, reconstructing the competitive reduction path into an ordered series channel, thereby improving urea selectivity.

[0024] (3) It exhibits excellent catalytic activity and energy efficiency, with a urea yield of 36249 μg·h under pulsed potential. -1 ·mg -1 It far surpasses existing Cu2O-based catalysts. The ECC strategy reduces energy consumption by nearly 31%, and TEA confirms its economic advantages. Near-zero carbon emissions can be achieved by using industrial nitrate wastewater as a nitrogen source.

[0025] (4) Breaking through the limitations of traditional catalysis, a new paradigm for intelligent regulation and conversion of CO2 is established. Co-designing "capture-release" and "reaction-coupling" sequences, Cu + Enhancing CN coupling efficiency at specific sites provides a novel technical pathway for green urea synthesis. Attached Figure Description

[0026] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein... Figure 1 These are characterization diagrams of the Cu / Cu2O@NCS catalyst obtained in Example 1 of this invention; wherein, a is a scanning electron microscope image, b is a transmission electron microscope image, c is an elemental distribution diagram, d is an X-ray diffraction pattern, e is a high-resolution X-ray photoelectron spectrum of Cu 2p, and f is a high-resolution X-ray photoelectron spectrum of N 1s.

[0027] Figure 2 This is an analysis of the electrochemical carbon capture-mediated CO2 reservoir characteristics of this invention; it includes cyclic voltammetry curves, comparisons of potential differences and local CO2 concentrations, and cyclic voltammograms of the interaction between pyridine radical anions and CO2. Specifically, a) shows the cyclic voltammograms of Cu / Cu2O@NCS and Comparative Example 1 in argon and CO2-saturated 1M potassium bicarbonate solution for p-benzoquinone; b) shows the potential difference (ΔE) and derived local CO2 concentrations of CS, NCS, Cu / Cu2O@NCS, and Cu / Cu2O@CS under two atmospheres; c) shows the cyclic voltammogram in a pyridine-containing dimethyl sulfoxide electrolyte; and d) shows the urea production performance of Cu / Cu2O@NCS and Cu / Cu2O@NCS.

[0028] Figure 3 The graph shows the catalytic performance results of the Cu / Cu2O@NCS catalyst obtained in Example 1; where a is a performance comparison graph of Cu / Cu2O@NCS catalysts with different copper loadings (5wt%, 10wt%, 20wt%, 30wt%); b is a urea yield graph under different pulse times; and c is a graph of the electrocatalytic performance test of the Cu / Cu2O@NCS catalyst.

[0029] Figure 4 This refers to the stability of the flow cell system in this invention.

[0030] Figure 5 It is a techno-economic assessment chart. Detailed Implementation

[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0032] Example 1:

[0033] This embodiment provides a method for preparing an electropulse-mediated electrochemical carbon capture type nitrogen-rich copper-based catalyst (Cu / Cu2O@NCS), comprising the following steps: (1) Preparation of carbon-shell precursor (CS): Using the modified Stöber method, 35 mL of tetraethyl orthosilicate (TEOS) and 300 mL of analytical grade ethanol were mixed and stirred until homogeneous to obtain solution A; 35 mL of 28 wt% concentrated ammonia was added to a mixture of 60 mL of deionized water and 150 mL of analytical grade ethanol and stirred until homogeneous to obtain solution B. Under vigorous stirring at 400 rpm, solution A was added dropwise to solution B at a rate of 1.5 mL / min, and the reaction was continued for 2 h after the addition was completed; then 5.6 mL of 40 wt% formaldehyde solution and 4 g of resorcinol were added to the mixture sequentially, and the reaction was continued to be stirred at room temperature for 24 h. The mixture was transferred to a 200 mL polytetrafluoroethylene-lined stainless steel reactor and reacted at 100 °C for 24 h; after cooling to room temperature, the obtained sample was washed three times by alternating centrifugation with deionized water and anhydrous ethanol, and then vacuum dried at 60 °C for 8 h to obtain carbon-shell precursor (CS).

[0034] (2) Preparation of nitrogen-doped carbon shell (NCS): The carbon shell precursor (CS) obtained in step (1) was mixed with melamine at a mass ratio of 1:5. The mixture was placed in a covered crucible and placed in a tube furnace. Under a nitrogen atmosphere with a purity ≥99.999%, the temperature was increased to 700℃ at a heating rate of 10℃ / min and calcined at a constant temperature for 1h. After calcination, the tube furnace was allowed to cool naturally to room temperature, and the sample was removed. The sample was placed in a 5M potassium hydroxide solution and stirred for 9h to remove some of the silica template. After the reaction was completed, the sample was centrifuged, washed with deionized water until the filtrate was neutral, and dried under vacuum at 60℃ for 6h to obtain nitrogen-doped carbon shell (NCS).

[0035] (3) Preparation of Cu / Cu2O@NCS catalyst: Weigh copper nitrate trihydrate (analytical grade) and 0.200g of NCS obtained in step (2), disperse them in a mixed solution of 10mL deionized water and 15mL analytical grade methanol, and control the copper loading in the catalyst to be 10wt%; place the mixed solution in an oil bath at 80℃ and heat it continuously until the water is completely evaporated to obtain a solid mixture. Place the solid mixture in a tube furnace and heat it to 400℃ at a heating rate of 5℃ / min under a nitrogen atmosphere, calcine it at a constant temperature for 2h, and then cool it naturally to room temperature to obtain the target catalyst Cu / Cu2O@NCS.

[0036] The structure of the obtained Cu / Cu2O@NCS catalyst was characterized, and the results are shown in the figure. Figure 1 : Figure 1 Characterization results for the Cu / Cu2O@NCS catalyst. Figure 1 Scanning electron microscopy (SEM) images show that the catalyst has a spherical structure with an average particle size of 200-300 nm. Figure 1The medium-b transmission electron microscope (TEM) image shows a distinct yolk-shell structure with a uniform thickness of 10-20 nm for the nitrogen-doped carbon shell. Figure 1 The distribution diagram of element C in the middle shows that elements such as Cu, N, and C are evenly distributed; Figure 1 The mid-d X-ray diffraction (XRD) pattern shows that 2θ=24.9° corresponds to the graphitic carbon (002) crystal plane, 36.4° and 42.3° correspond to the Cu2O (111) and (200) crystal planes, and 43.3° and 50.4° correspond to the Cu (111) and (200) crystal planes, confirming that Cu exists in the 0 and +1 valence states. Figure 1 The Cu 2p spectrum obtained by X-ray photoelectron spectroscopy (XPS) is consistent with the XRD results, and the characteristic peak of Cu2O / Cu was detected. Figure 1 The f N 1s spectrum confirmed the presence of pyridine nitrogen (398.5 eV), pyrrole nitrogen (400.3 eV), and graphitic nitrogen, among which pyridine nitrogen is a key active site for CO2 adsorption.

[0037] Example 2: This embodiment demonstrates the effect of different copper loadings on catalyst performance. Compared to Example 1, only the amount of copper nitrate trihydrate was changed to adjust the copper loading, as detailed below: (1) The preparation steps of carbon shell precursor (CS) and nitrogen-doped carbon shell (NCS) are completely consistent with steps (1)-(2) of Example 1.

[0038] (2) Prepare Cu / Cu2O@NCS catalysts with copper loading of 5wt%, 20wt%, and 30wt% respectively: Weigh the corresponding mass of copper nitrate trihydrate and mix with 0.200g NCS. The other reagents, reaction parameters and operation procedures are the same as in step (3) of Example 1. Prepare Cu / Cu2O@NCS-5%, Cu / Cu2O@NCS-20%, and Cu / Cu2O@NCS-30% catalysts respectively.

[0039] Comparative Example 1: Comparative Example 1 provides a method for preparing a Cu / Cu2O@CS catalyst (nitrogen-free control sample). Compared with Example 1, this comparative example does not introduce a nitrogen doping step, as detailed below: (1) The preparation steps of the carbon shell precursor (CS) are completely consistent with step (1) of Example 1.

[0040] (2) Preparation of Cu / Cu2O@CS catalyst: Weigh copper nitrate trihydrate and 0.200g of CS obtained in step (1), disperse them in a mixed solution of 10mL deionized water and 15mL methanol, and control the copper loading to 10wt%; the subsequent heating evaporation, tube furnace calcination (nitrogen atmosphere, heating to 400℃ at 5℃ / min, and holding at a constant temperature for 2h) are all consistent with step (3) of Example 1, and a nitrogen-free control sample Cu / Cu2O@CS is obtained.

[0041] Performance testing The catalysts obtained in the examples and comparative examples were subjected to performance tests, as detailed below: 1. Cu / Cu2O@NCS catalyst for electrochemical carbon capture-mediated CO2 concentration characteristics Figure 2 Analysis of the CO2 concentration characteristics of Cu / Cu2O@NCS catalysts used in electrochemical carbon capture-mediated CO2 concentration. Figure 2 In the figure, a represents the cyclic voltammetry curves of p-benzoquinone in Cu / Cu2O@NCS and Comparative Example 1 in 1M potassium bicarbonate solution saturated with argon and CO2. Figure 2 Figure b shows the potential difference (ΔE) of CS, NCS, Cu / Cu2O@NCS and Cu / Cu2O@CS under two atmospheres and the derived local CO2 concentration. It can be seen that the local CO2 concentration on the surface of Cu / Cu2O@NCS is 4.0 times higher than that of Cu / Cu2O@CS. Figure 2 In the figure, c represents the cyclic voltammogram of a pyridine-containing dimethyl sulfoxide electrolyte, -2.0V (vs. Fc). + The reduction peak at / Fc corresponds to the pyridine radical anion (Py· - The peak at -0.5V corresponds to Py-CO2. - The adduct decomposes and releases CO2, confirming the CO2 capture-release capability of the shell. Figure 2 The results in the study confirmed the superior urea production performance of the Cu / Cu2O@NCS surface, and also confirmed that the performance of Cu / Cu2O@CS was significantly lower than that of Cu / Cu2O@NCS.

[0042] 2. Catalytic performance tests with different copper ratios are shown below: The catalytic performance of different copper ratios is as follows: Figure 3 As shown, performance tests were conducted on catalysts prepared in Examples 1 and 2 with different copper loadings. The results are shown in the figure. Figure 3 As shown in Figure a: At a pulse potential of -0.6V (vs. RHE), the highest urea yield was achieved with a copper loading of 10wt%. Both excessively high and low loadings led to performance degradation. This is because insufficient loading resulted in fewer active sites, while excessive loading caused copper particle aggregation, masking the active sites. The best performance was achieved with a copper loading of 10wt%, yielding 36249 μg h⁻¹.-1 ·mg -1 ·cat.

[0043] 3. Catalytic performance study of Cu / Cu2O@NCS catalyst under different pulse potential parameters This embodiment investigates the effect of pulse potential parameters on catalytic performance. The catalyst preparation steps are exactly the same as in Example 1, except that the oxidation range (EO) of the pulse potential and the holding time of each potential range are changed. The specific pulse parameters are as follows:

[0044] Pulse parameters 1: negative potential range -0.6V (vs. RHE) held for 3-15s, oxidation potential range 0.3V (vs. RHE) held for 3-15s, pulse period 6-30s; results are shown in 3b, with the best performance when the pulse time is 10s.

[0045] 4. Electrocatalytic performance testing of Cu / Cu2O@NCS catalyst Comparison of catalytic performance between pulsed potential and static potential Using the Cu / Cu2O@NCS obtained in Example 1 as the working electrode, chronoamperometry was performed in the electrolyte (CO2-saturated 0.15 M KHCO3 and 1 M KHCO3 solutions) using pulsed potential (-0.6 V held for 10 s → 0.47 V held for 10 s) and static potential (-0.6 V), respectively. The results are shown in [Figure number missing]. Figure 3 c: The maximum urea yield under pulsed potential reached 36249 μg·h -1 ·mg -1 The efficiency is 3 times that of static potential testing, and the highest Faraday efficiency is 60% at 0V (vs. RHE).

[0046] Application example: Application of Cu / Cu2O@NCS catalysts in flow cell systems and industrial application evaluation I. Application Testing of Flow Cell System A two-electrode flow cell system was constructed, with a carbon felt loaded with Cu / Cu2O@NCS as the cathode and a RuO2-IrO2 / Ti mesh as the anode. The electrolyte was a mixed solution of potassium nitrate and potassium bicarbonate, and CO2 was introduced into the cathode at a rate of 60 sccm. Figure 4 The results showed that, compared with the H-type electrolytic cell, the urea yield in the flow cell system was increased by 8.4 times, and it could operate stably at a current of 0.5A for 32 hours, maintaining a urea yield of 18902 μg·h⁻¹. -1 It demonstrates good potential for industrial applications.

[0047] II. Technical and Economic Assessment (TEA) and Nitrogen Source Application Testing Figure 5This study presents a techno-economic evaluation of catalyst application using a daily urea production of 1 ton as the functional unit. It considers capital expenditure (CAPEX), operating expenditure (OPEX), and potential profit, exploring the impact of different nitrate sources (industrial nitrate wastewater and nitrogen electro-oxidation reaction). The results show that when using industrial nitrate wastewater as the nitrogen source, after including environmental compensation, the potential profit per ton of urea is US$181, achieving near-zero carbon emissions while realizing wastewater resource recovery, demonstrating both environmental value and economic feasibility.

[0048] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. The application of an electropulse-mediated electrochemical carbon-capturing nitrogen-rich copper-based catalyst in the electrocatalytic synthesis of urea from carbon dioxide and nitrate; the electrochemical carbon-capturing nitrogen-rich copper-based catalyst comprises a core-shell structure Cu / Cu2O@NCS, with a Cu / Cu2O composite phase as the core and a nitrogen-rich sp2O@NCS phase as the catalyst. 2 - The nitrogen-rich carbon layer with hybridized pyridine nitrogen sites forms a shell; in the Cu / Cu2O composite phase, Cu + The site is a key active site that promotes CN coupling; The preparation method of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst includes the following steps: S1. Mix silicon source with ethanol to obtain solution A; add alkaline substance to the mixed solvent to obtain solution B; mix solution A and solution B and react, then add formaldehyde solution and resorcinol to react to obtain a mixed solution; heat the obtained mixed solution to obtain a carbon shell precursor; S2. The obtained carbon shell precursor is mixed with a nitrogen source and calcined in an inert atmosphere. After cooling, the sample is placed in a template removal agent solution and stirred to obtain a nitrogen-doped carbon shell. S3. Disperse the copper source and the obtained nitrogen-doped carbon shell in a mixed solution, heat to evaporate the solution, and calcine the obtained solid under an inert atmosphere to obtain the electropulse-mediated electrochemical carbon capture type nitrogen-rich copper-based catalyst.

2. The application according to claim 1, characterized in that, The thickness of the shell layer is 20-30 nm; The particle size of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst is 100-500 nm; The loading of copper in the electrochemical carbon-capturing nitrogen-rich copper-based catalyst is 5-15 wt%.

3. The application according to claim 1, characterized in that, In step S1, the silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, and tetrabutyl orthosilicate; The alkaline substance includes one or more of concentrated ammonia, triethylamine, and ethanolamine; The mixing reaction time is 1.5-2.5 hours; The mixed solvents include deionized water and ethanol; The concentration of the alkaline substance is 25-28 wt%; The concentration of the formaldehyde solution is 37-40 wt%; The volume-to-mass ratio of the formaldehyde solution to resorcinol is (5.0-6.2):(3.5-4.5) mL / g; Heating reaction: temperature 90-110℃, time 22-26h.

4. The application according to claim 1, characterized in that, In step S2, the nitrogen source includes melamine and / or dicyandiamide; The mass ratio of the carbon shell precursor to the nitrogen source is 1:(4-6). Inert gases in an inert atmosphere include nitrogen and / or argon; Calcination conditions: heating rate of 8-12℃ / min, calcination temperature of 650-750℃, and calcination time of 0.8-1.2h; The template removal agent solution includes one or more of potassium hydroxide solution, sodium hydroxide solution, and hydrofluoric acid solution; The stirring time is 8-10 hours.

5. The application according to claim 1, characterized in that, In step S3, the copper source is selected from one or more of hydrated copper nitrate, copper chloride, copper sulfate, and copper acetate; The mass ratio of the copper source to the nitrogen-doped carbon shell is (5-30):1; The mixture comprises water and methanol in a volume ratio of (4-6):(6-9). The heating temperature is 75-85℃; The inert gas in the inert atmosphere is selected from nitrogen and / or argon; Heating and roasting conditions: heating rate of 4-6℃ / min, temperature of 380-420℃, and time of 1.8-2.2h.

6. The application according to claim 1, characterized in that, The application includes the following steps: The electrochemical carbon-capturing nitrogen-rich copper-based catalyst, binder, and conductive agent are mixed, and a solvent is added to form a slurry. This slurry is then coated onto the surface of a conductive substrate and vacuum dried to obtain the working electrode. A three-electrode system was constructed using the working electrode as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. An H-type electrolytic cell or a flow cell was used as the reaction device, a mixed solution of bicarbonate and nitrate was used as the electrolyte, and carbon dioxide was introduced. Applying a pulsed potential mode for energization, the negative potential range of -0.6V to -0.4V vs RHE achieves CO2 capture and nitrate pre-activation, while the oxidation potential range of 0.3V to 0.47V vs RHE releases CO2 and triggers the CN coupling reaction.

7. The application according to claim 6, characterized in that, The mass ratio of the electrochemical carbon-capturing nitrogen-rich copper-based catalyst, binder, and conductive agent is (8-9):(0.5-1):(0.5-1). The coating amount of the slurry is 0.05-2 mg / cm². 2 The vacuum drying temperature is 60-80℃, and the time is 8-12 hours; The binder is one or more of Nafion reagent, polyvinylidene fluoride, or perfluorosulfonic acid resin; the conductive agent is acetylene black and / or Ketjen black; the conductive substrate is carbon paper or copper foil. The electrolyte contains 0.1-1.5 M of bicarbonate and 0.05-1.0 M of nitrate. The bicarbonate is potassium bicarbonate and / or sodium bicarbonate, and the nitrate is one or more of potassium nitrate, sodium nitrate, and industrial nitrate wastewater.

8. The application according to claim 7, characterized in that, In the pulsed potential mode, each potential interval is held for 10-60 seconds, and the pulse period is 20-120 seconds. During the reaction, the electrolyte temperature is controlled at 25-60℃, and the carbon dioxide introduction rate is 10-50 mL / min.

Citation Information

Patent Citations

  • Method and device for preparing urea through pulse electrochemical catalysis C-N coupling

    CN118109835A